CLINICAL PRESENTATION, RISK FACTORS AND OUTCOME OF STROKE AT A DISTRICT LEVEL TEACHING HOSPITAL - Masood, Choudhary Tariq; Hussain, Maqbool; Rehman, Anis -ur-; Abbasi, Saleem (Journal of Ayub Medical College Abbottabad, 2013)
Background: Stroke is a fatal clinical syndrome with mortality rate ranging up to 25%. Hypertension, smoking and diabetes mellitus are common preventable risk factors which are associated with serious outcome. Objective of this study was to determine the clinical presentation, risk factors and outcome of stroke. Methods: A cross-sectional study was conducted in the Medical Wards of DHQ Teaching Hospital, Mirpur Azad Kashmir from March 2010 to January 2011. A questionnaire was prepared in accordance with the objectives of the study. Frequency of risk factors in patients with stroke were studied. Different clinical features were also noted and response to the given treatment was checked in the form of mortality and recovery. Frequencies and percentages were calculated using SPSS-12. Results: Two hundred patients with stroke were selected. Of the total, 136 (68%) had hypertension, 55 (27.5%) were smokers, 53 (26.5%) had diabetes and 25 (12.5%) patients had ischemic heart disease. One hundred and two (51%) patients presented with headache, 99 (49.5%) developed hemiplegia and 94 (47%) had loss of consciousness. CT brain showed infarction in 144 (72%) patients while 56 (28%) had haemorrhage. Observed mortality in this study was 18 (9%) while 182 (91%) patients were discharged after treatment. Conclusion: Hypertension, smoking and diabetes mellitus are major modifiable risk factors for stroke. Headache, hemiplegia and loss of consciousness are major clinical features. Ischemic stroke is much common compared to hemorrhagic stroke. With proper care stroke is manageable satisfactorily. Keywords: Stroke, risk factors, outcome